Strategi Komunikasi Publik Pengelola Wisata Religi Masjid Raya Al Mashun Medan dalam Meningkatkan Minat Wisatawan - Uchie, Uchie; Deni, Indira Fatra (Unitri Press, 2025)
This study aims to analyze the public communication strategies employed by the management of Al Mashun Grand Mosque in Medan to enhance tourist interest in the mosque as a religious tourism destination. Using a qualitative approach, data were collected through interviews, observations, and documentation. The study adopts the marketing mix theory within the context of tourism communication. The findings indicate that the mosque management still relies heavily on personal communication approaches and the mosque’s historical image, with suboptimal utilization of social media platforms. Friendly service and direct information transparency serve as key strengths in attracting tourists. However, limitations in human resources for digital content management and the lack of educational narratives present challenges in modernizing public communication efforts. The study recommends the formation of a dedicated team for digital media management, development of educational content, and collaborative promotion with the government and creative communities. These efforts are essential for enabling Al Mashun Grand Mosque to adapt to technological advancements and become a leading and sustainable religious tourism destination. Abstrak Penelitian ini bertujuan untuk menganalisis strategi komunikasi publik yang diterapkan oleh pengelola Masjid Raya Al Mashun Medan dalam upaya meningkatkan minat wisatawan sebagai destinasi wisata religi. Dengan pendekatan kualitatif, data dikumpulkan melalui wawancara, observasi, dan dokumentasi. Penelitian ini menggunakan perspektif teori marketing mix dalam kajian komunikasi pariwisata. Hasil penelitian menunjukkan bahwa pengelola masih mengandalkan pendekatan komunikasi personal dan citra historis masjid, dengan pemanfaatan media sosial yang belum optimal. Strategi pelayanan ramah dan keterbukaan informasi secara langsung menjadi kekuatan utama dalam menarik wisatawan. Namun, keterbatasan sumber daya manusia dalam pengelolaan konten digital dan kurangnya narasi edukatif menjadi tantangan dalam transformasi komunikasi publik yang lebih modern. Penelitian ini merekomendasikan membentuk tim untuk pengelolaan media digital dan pengembangan konten edukatif serta promosi kolaboratif dengan pemerintah dan komunitas kreatif, agar Masjid Raya Al Mashun mampu beradaptasi dengan perkembangan teknologi dan menjadi destinasi wisata religi unggulan yang berkelanjutan.